The Procoagulant State of the VX-2 Tumor in Rabbit Lung In Vivo - Hatton, Mark W. C.; Ross, Bonnie; Bardossy, Leslie; Southward, Suzanne M. R.; DeReske, Marnie; Richardson, Mary; Blajchman, Morris A. (Thrombosis and Haemostasis, 1999)
During their growth, many malignant solid tumors elicit a hemostatic response in the host. In this report, the fluxes of various rabbit plasma hemostatic proteins into pulmonary VX-2 tumors have been measured in vivo. VX-2 cells were contained within a small rabbit plasma clot which was injected intravenously into rabbits. At 28 d, each rabbit was injected intravenously with two radiolabeled (131I, 125I) proteins selected from fibrinogen, prothrombin, antithrombin-α, heparin cofactor II, or plasminogen-I or -II. After allowing the labeled proteins to circulate for 10-200 min, each rabbit was perfused with Krebs-Henseleit solution and the lungs excised. Solid tumors were isolated, weighed and measured for radioactivity content. A mean of 14 tumors/pair of lungs with a mean tumor weight of 0.3 g was obtained. Radioactivity per g of tumor was related to radioactivity/ml of blood at exsanguination for each protein at each time interval. Maximum flux rates were calculated (as pmol/g of tumor/min): Fibrinogen, 65.0; prothrombin, 53.0; antithrombin-α, 24.1; HCII, 17.2; plasminogen-II, 5.0; and plasminogen-I, 3.2. Using immunocytochemical staining, fibrin(ogen) was distributed heterogeneously within the VX-2 tumor, appearing largely in the perinodular region and in the necrotic core. From the net fluxes of these proteins, the profile of chronic hemostasis associated with the VX-2 tumor was shown to differ markedly from the hemostatic response that occurs after an acute vascular injury.
Keywords: Tumor; procoagulant state; hemostasis factors; fibrinogen